TYPOLOGY OF CONJUNCTIONS IN THE EASTERN CURSE REGIONAL LANGUAGE (CASE STUDY OF STUDENTS OF INDONESIAN LANGUAGE STUDY PROGRAM FKIP UNKHAIR - Anwar Nada; Rustam Hasim (Fakultas Keguruan Dan Ilmu Pendidikan Universaitas PGRI Banyuwangi, 2026)
This study aims to describe the typology of conjunctions in the regional languages of East Makian with a focus on the classification of forms, syntactic functions, and relational meanings that appear in the use of language by students of the Indonesian Language Education Study Program, FKIP Khairun University. The East Makian language, also known as Taba or Makian Dalam, is a regional language spoken in the Makian and South Halmahera Island areas, North Maluku Province. The existence of this language is important to study because it is still alive in a spoken society, but it is in a situation that demands documentation and strengthening intergenerational functions. This research is prepared as a qualitative descriptive study with a structural-functional linguistic approach. The focus of the discussion was directed at the types of conjunctions that have the potential to appear in the speech of East Makian speakers, namely coordinated, subordinative, correlative, interclause, and intersentence conjunctions. Because specific documentation on East Makian conjunctions is still limited in available online sources, the typology discussion is compiled through the combination of basic linguistic data about East Makian with the framework of conjunction theory in Indonesian linguistics to produce an analysis model that can be used in advanced field research. The results of the study show that the typology of conjunctions in the Eastern Makian language can be conceptually mapped based on the relationship of addition, selection, contradiction, cause, condition, goal, time, and order between syntactic units. In the context of FKIP Unkhair students, the use of regional conjunctions is expected to be present side by side with Indonesian conjunctions due to the bilingual situation and language contact. Thus, research on Eastern Makian conjunctions is not only important for grammatical description, but also relevant for the preservation of regional languages, the teaching of regional linguistics, and the strengthening of students' linguistic identity.